High co-prevalence of genogroup 1 TT virus and human papillomavirus is associated with poor clinical outcome of laryngeal carcinoma. Issue 4 (24th March 2005) - Szládek, G; Juhász, A; Kardos, G; Szőke, K; Major, T; Sziklai, I; Tar, I; Márton, I; Kónya, J; Gergely, L; Szarka, K
Abstract : Background: The aetiology and factors leading to the progression of laryngeal cancer are still unclear. Although human papillomavirus (HPV) has been suggested to play a role, reports concerning the effect of HPV infection on tumour development are controversial. Recently, transfusion transmitted virus (TTV) was suggested to play a role in certain infections as a causative or coinfecting agent. Aims: To investigate whether the development and progression of laryngeal squamous cell carcinoma is associated with coinfection with TTV and HPV. Methods: The prevalence of TTV and HPV was investigated using the polymerase chain reaction in tissue samples from 40 healthy individuals, 10 patients with recurrent papillomatosis, five patients with papillomatosis with malignant transformation, and 25 patients with laryngeal carcinoma. The obtained prevalence data were compared and analysed statistically. Results: In the 11 patients with carcinoma who had metastasis or relapse there was a high rate of coinfection with genogroup 1 TTV and HPV (eight of 11), whereas in the 14 without tumour progression no coinfection was found. Coinfection was associated with significantly lower tumour free survival in patients with carcinoma (p < 0.001). Furthermore, four of five patients who had papillomatosis with malignant transformation were coinfected with genogroup 1 TTV and HPV. Conclusions: Although the nature of cooperation between HPV and TTV needs to be investigated further, coinfection with genogroup 1 TTV and HPV appears to be associated with poor clinical outcome in laryngeal cancer.